The Spore door - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Spore doorSpore s never a bore.Bring Spore to the fore.Spore has something in store.Spore s a mine of ore.Always news still with insights galore!Thomas Schwiedessen, Ghana